The Importance Of Implementing Integrated Coaching Post (Posbindu) For Non-Communicable Diseases (Ncd) For Staff At The Kader Bangsa University (Ukb) Palembang - Utari, Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Non-communicable diseases (NCDs) are the leading cause of death, accounting for 36 million (63%) of all deaths worldwide, with approximately 29 million (80%) occurring in developing countries (WHO, 2010). The future increase in NCD deaths is projected to continue at 15% (44 million deaths) between 2010 and 2020. This is due to population growth and increased life expectancy, particularly in developing countries. Furthermore, changes in human behavior and unhealthy environments are contributing to the increase in NCDs. Data on NCDs in Indonesia for 2025 shows that NCDs remain a major health problem, with high mortality rates and a leading cause of disability. Recent data indicate that NCDs, including heart disease, stroke, diabetes, and kidney failure, contribute significantly to the disease burden in Indonesia. NCDs are responsible for 75% of deaths in Indonesia. Non-communicable diseases (NCDs) can be prevented through controlling risk factors, namely smoking, lack of physical activity, unhealthy diet, and alcohol consumption. Increasing public awareness and concern about NCD risk factors is crucial for controlling NCDs. Therefore, community empowerment and participation are needed, known as the Integrated Community Development Program (Posbindu) for Non-Communicable Diseases (NCDs). The purpose of this program is to determine the health status of personnel (male and female) at Universitas Kader Bangsa (UKB) Palembang, as well as the community within the Universitas Kader Bangsa (UKB) Palembang area through the Integrated Community Service Post (Posbindu).